2010
DOI: 10.3390/medicina46070067
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thoracic epidural anesthesia on liver hemodynamics in patients under general anesthesia

Abstract: Background and objective. Hepatic hypoperfusion is regarded as an important factor in the pathophysiology of perioperative liver injury. Although thoracic epidural anesthesia is a widely used technique, limited data are available about the effects on hepatic blood flow with blockade restricted to thoracic segments in humans. The main objective of the present study was to investigate the effects of thoracic epidural anesthesia on hepatic blood flow under general anesthesia in humans. Material and methods. In 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Thoracic epidural anesthesia flow, finding that TEA reduced blood flow to the liver, fluid resuscitation alone could not reverse this effect but had to be associated with dopamine infusion. Trepenaitis et al [24] found a reduction of PDRICG in patients undergoing upper abdominal surgery with TEA. This data was not associated with a fall in CO and could not be reversed by administration of vasopressors.…”
Section: Rabbits Hoganmentioning
confidence: 97%
See 3 more Smart Citations
“…Thoracic epidural anesthesia flow, finding that TEA reduced blood flow to the liver, fluid resuscitation alone could not reverse this effect but had to be associated with dopamine infusion. Trepenaitis et al [24] found a reduction of PDRICG in patients undergoing upper abdominal surgery with TEA. This data was not associated with a fall in CO and could not be reversed by administration of vasopressors.…”
Section: Rabbits Hoganmentioning
confidence: 97%
“…Three studies [24] used centrally injected radio active or colored microspheres to determine cardiac output and regional blood flow. The regional flow could be estimated by measuring organ or regional arterial blood samples radioactivity, or by microscopy after autopsy.…”
Section: Effects Of Epidural Anesthesia On Splanchnic Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hypotension is the result of decrease in systemic vascular resistance, and this may reduce hepatic blood flow. Lumbar thoracic anesthesia is shown to reduce liver blood flow in nonhuman and human studies [2]. Patients undergoing major abdominal surgery, such as hepatectomy, are at risk for postoperative complications, including multiple organ failure.…”
mentioning
confidence: 99%